Covid-19 Pandemic: challenges and management in dentistry A Cross-Sectional Study in Sirte, Libya - Ali, Abdalmawla Alhussin; Belgasem, Karima Ali; Etbiga, Abdalla Mohamed (Journal of medical and pharmaceutical sciences, 2022)
In order to protect the team and the patients and stop the virus from spreading, it is crucial that dentists improve their knowledge and preventative measures because they come into direct and close contact with the patient aerosols. Aim: This study aimed to evaluate the impact of coronavirus (COVID-19) pandemic on dental practice by conducting a questionnaire among the Libyan dental practitioners. Materials and Methods: Our study population consisted of dentists, a questionnaire was distributed to 50 dentist (36 female and 14 male) the questionnaire was assessing knowledge, attitude, risk perception, and preparedness towards COVID-19, infection control measures and assessing dentist’s fear potential financial loss and the risk of being infected. Results: The study sample included 50 dentists, and the majority of participants were knowledgeable about COVID-19’s transmission, incubation time, and primary symptoms. In addition, 72% of participants updated the WHO’s current cross-infection guidelines for COVID-19. Conclusion: Although dentists’ knowledge of COVID-19 is generally adequate, it should be made better in order to improve patients management and stop the spread of COVID-19.